1998
DOI: 10.1007/s002800050818
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of intestinal microflora β-glucuronidase modifies the distribution of the active metabolite of the antitumor agent, irinotecan hydrochloride (CPT-11) in rats

Abstract: These results suggest that SN-38, which results from the hydrolysis of SN-38 glucuronide by beta-glucuronidase in the intestinal microflora, contributes considerably to the distribution of SN-38 in the large intestine tissue, and that inhibition of the beta-glucuronidase activity by antibiotics results in decreased accumulation of SN-38 in the large intestine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
108
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(109 citation statements)
references
References 18 publications
0
108
1
Order By: Relevance
“…TMA is absorbed and oxidized by hepatic flavin monooxygenases to form TMA N-oxide (TMAO), a metabolite linked to increased accumulation of cholesterol in macrophages, foam cell deposition, and atherosclerosis (72). Clinical studies have confirmed that TMAO production is also dependent on the gut microbiome in humans, with plasma TMAO levels suppressed during antibiotic treatment and restored upon contributing to dose-limiting gastrointestinal side effects (47,48). Broad-spectrum antibiotics and dietary fiber consumption have been proposed as general strategies that might reduce the toxicity of irinotecan (49,50), but both of these interventions can have widespread impacts on the gut microbiota (51,52).…”
Section: R E V I E W S E R I E S : G U T M I C R O B I O M Ementioning
confidence: 99%
“…TMA is absorbed and oxidized by hepatic flavin monooxygenases to form TMA N-oxide (TMAO), a metabolite linked to increased accumulation of cholesterol in macrophages, foam cell deposition, and atherosclerosis (72). Clinical studies have confirmed that TMAO production is also dependent on the gut microbiome in humans, with plasma TMAO levels suppressed during antibiotic treatment and restored upon contributing to dose-limiting gastrointestinal side effects (47,48). Broad-spectrum antibiotics and dietary fiber consumption have been proposed as general strategies that might reduce the toxicity of irinotecan (49,50), but both of these interventions can have widespread impacts on the gut microbiota (51,52).…”
Section: R E V I E W S E R I E S : G U T M I C R O B I O M Ementioning
confidence: 99%
“…[Takasuna et al 1998;Stringer et al 2007Stringer et al , 2008. (3) The distribution and severity of histological damage within the rat intestine after administration of irinotecan has been correlated to the luminal ß-glucuronidase activity in rodents [Takasuna et al 1998;Fittkau et al 2004]. (4) Irinotecan causes severe colonic damage (increased apoptosis, crypt hypoplasia and dilation) with accompanying excessive mucous secretion, as well as the usual chemotherapy-induced small intestinal damage, like villous atrophy and crypt hypoplasia.…”
Section: Pathophysiology Of Irinotecan-induced Diarrheamentioning
confidence: 99%
“…The bacterial ß-glucuronidase then deconjugates SN38G to the active form SN38 at an increased rate causing significant damage and diarrhea. [Takasuna et al 1998;Stringer et al 2007Stringer et al , 2008. (3) The distribution and severity of histological damage within the rat intestine after administration of irinotecan has been correlated to the luminal ß-glucuronidase activity in rodents [Takasuna et al 1998;Fittkau et al 2004].…”
Section: Pathophysiology Of Irinotecan-induced Diarrheamentioning
confidence: 99%
“…Prophylactic use of antibiotics in rats reduced both SN-38 concentration in the intestinal lumen and diarrhea (11). Administration of antibiotics in man reduced both fecal h-glucuronidase activity and the SN-38/SN-38 glucuronide ratio (12) although available data on the efficacy of this prophylactic treatment on diarrhea are inconclusive (12,13).…”
mentioning
confidence: 99%